2021
DOI: 10.15829/1728-8800-2021-2965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regional living conditions on middle-term cardiovascular outcomes: data from prospective stage of the ESSE-RF study

Abstract: Aim. To assess regional living conditions with cardiovascular outcomes based on prospective stage of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study.Material and methods. We used data from a 3- and 5-year prospective stage of the ESSE-RF study (2012-2013). For initial screening, 16210 people aged 25-64 were included. To characterize the regions of residence, 5 regional indices (RIs) were used. The following endpoints were considered: cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
3
1
0
Order By: Relevance
“…An increase in the odd of major ECG abnormalities revealed in men in demographically depressed regions was consistent with previously obtained data on the increase in cardiovascular risk over a 3-year follow-up period 41 . As in the prospective study, an impact of the Demographic Index was less pronounced (compared with the Industrial Index and Mixed Index), which could be due to indirect mediation by other spatial characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An increase in the odd of major ECG abnormalities revealed in men in demographically depressed regions was consistent with previously obtained data on the increase in cardiovascular risk over a 3-year follow-up period 41 . As in the prospective study, an impact of the Demographic Index was less pronounced (compared with the Industrial Index and Mixed Index), which could be due to indirect mediation by other spatial characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous published data confirmed the effect of ambient air pollution on cardiovascular morbidity and mortality 37,38 ; the latter is also characteristic of industrial pollution 39,40 . Previously, on the same sample as in this study, we revealed that the growth of the regional industrial development was associated with an increase in the odd of developing myocardial infarction and overall cardiovascular risk in a 5-year prospective follow-up 41 . Therefore, the obtained results exhibited negative impact of anthropogenic pollution on the myocardium, which manifested itself to a greater extent in severe (major) ECG abnormalities.…”
Section: Discussionmentioning
confidence: 50%
“…An increase in the likelihood of major ECG abnormalities revealed in men in demographically depressed regions was consistent with previously obtained data on the increase in cardiovascular risk over a 3-year follow-up period [42]. As in the prospective study, an impact of the Demographic Index was less pronounced (compared with the Industrial Index and Mixed Index), which could be due to indirect mediation by other spatial characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous published data con rmed the effect of ambient air pollution on cardiovascular morbidity and mortality [38,39]; the latter is also characteristic of industrial pollution [40,41]. Previously, on the same sample as in this study, we revealed that the growth of the regional industrial development was associated with an increase in the likelihood of developing myocardial infarction and overall cardiovascular risk in a 5-year prospective follow-up [42]. Therefore, the obtained results exhibited negative impact of anthropogenic pollution on the myocardium, which manifested itself to a greater extent in severe (major) ECG abnormalities.…”
Section: Discussionsupporting
confidence: 71%